Patterns of modern pollen and plant richness across northern Europe. (11th February 2019) - Reitalu, Triin; Bjune, Anne E.; Blaus, Ansis; Giesecke, Thomas; Helm, Aveliina; Matthias, Isabelle; Peglar, Sylvia M.; Salonen, J. Sakari; Seppä, Heikki; Väli, Vivika; Birks, H. John B.
Abstract: Sedimentary pollen offers excellent opportunities to reconstruct vegetation changes over past millennia. Number of different pollen taxa or pollen richness is used to characterise past plant richness. To improve the interpretation of sedimentary pollen richness, it is essential to understand the relationship between pollen and plant richness in contemporary landscapes. This study presents a regional‐scale comparison of pollen and plant richness from northern Europe and evaluates the importance of environmental variables on pollen and plant richness. We use a pollen dataset of 511 lake‐surface pollen samples ranging through temperate, boreal and tundra biomes. To characterise plant diversity, we use a dataset formulated from the two largest plant atlases available in Europe. We compare pollen and plant richness estimates in different groups of taxa (wind‐pollinated vs. non‐wind‐pollinated, trees and shrubs vs. herbs and grasses) and test their relationships with climate and landscape variables. Pollen richness is significantly positively correlated with plant richness ( r  = 0.53). The pollen plant richness correlation improves ( r  = 0.63) when high pollen producers are downweighted prior to estimating richness minimising the influence of pollen production on the pollen richness estimate. This suggests that methods accommodating pollen‐production differences in richness estimates deserve further attention and should become more widely used in Quaternary pollen diversity studies. The highest correlations are found between pollen and plant richness of trees and shrubs ( r  = 0.83) and of wind‐pollinated taxa ( r  = 0.75) suggesting that these are the best measures of broad‐scale plant richness over several thousands of square kilometres. Mean annual temperature is the strongest predictor of both pollen and plant richness. Landscape openness is positively associated with pollen richness but not with plant richness. Pollen richness values from extremely open and/or cold areas where pollen production is low should be interpreted with caution because low local pollen production increases the proportion of extra‐regional pollen. Synthesis. Our results confirm that pollen data can provide insights into past plant richness changes in northern Europe, and with careful consideration of pollen‐production differences and spatial scale represented, pollen data make it possible to investigate vegetation diversity trends over long time‐scales and under changing climatic and habitat conditions. Abstract : Our results confirm that pollen data can provide insights into past plant richness changes in northern Europe, and with careful consideration of pollen‐production differences and spatial scale represented, pollen data make it possible to investigate vegetation diversity trends over long time‐scales and under changing climatic and habitat conditions. Kokkuvõte: Taimede ja õietolmu liigirikkuse seosed Põhja‐Euroopas Järvede ja soode settes leiduva õietolmu abil rekonstrueeritakse viimaste kümnete tuhandete aastate taimkatte muutusi. Soontaimede liigirikkust minevikus hinnatakse tihti erinevate õietolmutüüpide arvu alusel. Õietolmu ja taimede liigirikkuse seoste uurimine tänapäeva maastikes aitab sette õietolmuandmeid paremini tõlgendada. Käesolevas uuringus keskendume õietolmu ja taimede liigirikkuse seostele Põhja‐Euroopas ja hindame erinevate keskkonnategurite mõju nii taimede ja kui õietolmu liigirikkusele. Uuringus kasutatav õietolmu andmestik pärineb 511 järve pinnasettest ja vaadeldav piirkond ulatub parasvöötmest tundrani. Soontaimede liigirikkuse hindamiseks kasutame andmeid kahest Euroopa taimede levikuatlasest. Võrdleme õietolmu ja taimede liigirikkust erinevates taimerühmades (tuultolmlejad vs. mitte tuultolmlejad, puud ja põõsad vs. rohttaimed) ja testime liigirikkuste seoseid kliimat ja maastiku struktuuri iseloomustavate tunnustega. Leidsime, et õietolmu liigirikkus ja soontaimede liigirikkus on positiivselt korreleerunud ( r  = 0.53). Õietolmu ja taimede liigirikkuse korrelatsioon paraneb ( r  = 0.63) kui korrigeerime õietolmu andmestikku, vähendades suurte õietolmutootjate (näiteks kask ja mänd) osatähtsust. Siit järeldub, et kasutades õietolmu liigirikkuse hinnanguid mineviku andmetes, tuleks arvesse võtta liikidevahelised õielmu tootlikkuse erinevused. Kõige tugevamad korrelatsioonid taimede ja õietolmu liigirikkuste vahel on puudel ja põõsastel ( r  = 0.83) ja tuultolmlejatel ( r  = 0.75). Meie tulemuste põhjal on just nende taimerühmade õietolmu liigirikkused sobivaimad taimede regionaalse liigirikkuse muutuste tuvastamiseks. Nii õitolmu kui taimede liigirikkus on tugevasti seotud aasta keskmise õhutemperatuuriga. Maastiku avatus on positiivselt seotud õietolmu liigirikkusega, aga mitte taimede liigirikkusega. Täiesti avatud maastikes ja/või külma kliimaga aladel, kus kohalik õietolmu tootlikkus on väga madal, mõjutab õietolmu liigirikkuse hinnanguid regiooni välise õietolmu suur osatähtsus. Kokkuvõtteks . Meie tulemused kinnitavad, et õietolmu andmed võimaldavad uurida taimede liigirikkuse muutusi Põhja‐Euroopas. Võttes arvesse õietolmu tootlikkuse erinevusi ja ruumilist skaalat, mida andmestik peegeldab, võimaldavad õietolmu andmed uurida taimede liigirikkuse pikaajalisi muutusi ja liigirikkuse seoseid mineviku kliima ja keskkonnatingimustega.